2021
DOI: 10.3390/genes13010089
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Transcriptomic and Serological Differences between Forced Molting and Natural Molting in Laying Hens

Abstract: Molting is natural adaptation to climate change in all birds, including chickens. Forced molting (FM) can rejuvenate and reactivate the reproductive potential of aged hens, but the effect of natural molting (NM) on older chickens is not clear. To explore why FM has a dramatically different effect on chickens compared with NM, the transcriptome analyses of the hypothalamus and ovary in forced molted and natural molted hens at two periods with feathers fallen and regrown were performed. Additionally, each experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…There was a little difference between the two moult modes, forced and spontaneous in the terms of feather coverage, but the appearance of the ovaries varied greatly (Zhang et al, 2022). According to Zhang et al (2022), generally, it would take 14-16 weeks to complete natural moult, whereas forced moult can be completed in 4 weeks for chickens without being affected by seasons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a little difference between the two moult modes, forced and spontaneous in the terms of feather coverage, but the appearance of the ovaries varied greatly (Zhang et al, 2022). According to Zhang et al (2022), generally, it would take 14-16 weeks to complete natural moult, whereas forced moult can be completed in 4 weeks for chickens without being affected by seasons.…”
Section: Resultsmentioning
confidence: 99%
“…There was a little difference between the two moult modes, forced and spontaneous in the terms of feather coverage, but the appearance of the ovaries varied greatly (Zhang et al, 2022). According to Zhang et al (2022), generally, it would take 14-16 weeks to complete natural moult, whereas forced moult can be completed in 4 weeks for chickens without being affected by seasons. Our monitoring confirms that the duration of natural moult in chickens in the industrial system exceeds the duration of the eight weeks of monitoring since at the end of the eight weeeks of surveillance, the naturally moulted hens had statistically significantly lower both laying percentage and body weight vs. control group (P = 0.009 and P = 0.043, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, FM achieved the rejuvenation effect in laying hens, and reproductive organs showed senescence under hunger stress and redeveloped after water supply and feeding were restored [ 29 , 32 ]. Further studies have revealed that this process is accompanied by the regulation of DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…The farming method, known as the fasting method, capitalizes on the reduced feed intake characteristic during the natural molting phase of poultry. It involves a period of fasting, water restriction, and adjustment of the lighting schedule to stimulate the flock, facilitating a prompt transition of laying hens into a new egg-laying cycle [ 3 , 6 ]. The hormone method entails injecting adrenal hormones, thyroid hormones, and progesterone into the muscle of poultry, resulting in a hormonal imbalance, perturbing the physiological equilibrium, and prompting laying hens to cease egg production and undergo molting [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%